Pengaruh Dosis Pupuk NPK Phonska terhadap Produksi Bawang Merah (Allium ascalonicum L) - Yosep Marutop; Irba Djaja; Abdullah Sarijan (Musamus University, 2019)
The discussion focused on the effect of NPK fertilizer named Phonska on the growth rate of red onion, and the crops production. In this study, the method used is descriptive study lasted three months, from July 2011 to October 2011. The data collection techniques used in the preparation of this paper is a randomized block design (RBD ) and documentation . Based on the results, this study showed that the effect of NPK fertilizer Phonska on onion production are very significant. Phonska influence the number of tillers, because it meet the nutrient needs of plants so the crops able to produce well. For better results in the production of red onions we suggested that the cultivation of onion crop use NPK Phonska because it influence the development of onion growth. We recomended the relevant institutions to distribute NPK fertilizer and applying Phonska on onion crop growth to increase the production.